Manejo Agronómico de cultivo de algodón (Gossypium barbadense L.), en la Empresa Agrícola Cerro Prieto S.A.C - Pairazaman Vites, Eder Eduardo (2012)
Between January and April 2011 was conducted fieldwork with the objective of the company described as Agricultural Cerro Prieto S.A.C. being made by the agricultural management of cotton in which the company shows a disruptive technology compared withthat of other empirical planting area farmers. In this he founded the first planting and fertilization is machined 1500 ha being planted. Hazera varieties, IPA and Delta, the drip irrigation was and has sophisticated fertigation equipment, applications of chemicals (pesticides and foliar) is made by pulverizing machines very full and the harvest is mechanized and anual which yields obtained over the 125 qq. In this way the company shows how important it is to have a very sophisticated technology at the national level and thanks to exports of cotton that are most in demand each year.